STRATEGI KOMUNIKASI PEMASARAN BATIK GONGGONG “LAWANA” TANJUNGPINANG DALAM MEMBANGUN BRAND AWARENESS - Ajura Nur; Muhammad Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The term of gonggong sounds foreign or strange impression for people outside the Kepulauan Riau. But for people in the Kepulauan Riau, is no stranger to this one sea slug. Gonggong (Strombus Turturella) is one of the many sea slug that are found around the Kepri waters. Batik Gonggong is new textile design in Indonesia. In 2010 open Selaras Shop as a manufacturer of batik gonggong with the brand